Fiber optical imaging of astroglial calcium signaling in the respiratory network in the working heart brainstem preparation - Tacke, Charlotte; Bischoff, Anne M.; Harb, Ali; Vafadari, Behnam; Hülsmann, Swen (Frontiers in Physiology, 2023)
The neuronal activity in the respiratory network strongly depends on a variety of different neuromodulators. Given the essential role of astrocytes in stabilizing respiratory network activity generated by neurons in the preBötzinger complex (preBötC), our aim was to investigate astrocytic calcium signaling in the working heart brainstem preparation using fiber-optical imaging. By using transgenic mice that express GCaMP6s specifically in astrocytes, we successfully recorded astrocytic calcium signals in response to norepinephrine from individual astrocytes.